Spontaneous ordering of identical materials into a triboelectric series - Juan Carlos Sobarzo; Felix Pertl; Daniel M. Balazs; Tommaso Costanzo; Markus Sauer; Annette Foelske; Markus Ostermann; Christian M. Pichler; Yongkang Wang; Yuki Nagata; Mischa Bonn; Scott Waitukaitis (Nature, 2025)
Abstract When two insulating, neutral materials are contacted and separated, they exchange electrical charge 1 . Experiments have long suggested that this ‘contact electrification’ is transitive, with different materials ordering into ‘triboelectric series’ based on the sign of charge acquired 2 . At the same time, the effect is plagued by unpredictability, preventing consensus on the mechanism and casting doubt on the rhyme and reason that series imply 3 . Here we expose an unanticipated connection between the unpredictability and order in contact electrification: nominally identical materials initially exchange charge randomly and intransitively, but—over repeated experiments—order into triboelectric series. We find that this evolution is driven by the act of contact itself—samples with more contacts in their history charge negatively to ones with fewer contacts. Capturing this ‘contact bias’ in a minimal model, we recreate both the initial randomness and ultimate order in numerical simulations and use it experimentally to force the appearance of a triboelectric series of our choosing. With a set of surface-sensitive techniques to search for the underlying alterations contact creates, we only find evidence of nanoscale morphological changes, pointing to a mechanism strongly coupled with mechanics. Our results highlight the centrality of contact history in contact electrification and suggest that focusing on the unpredictability that has long plagued the effect may hold the key to understanding it.